Pengaruh Dana Alokasi Umum, dan Pendapatan Asli Daerah Terhadap Tingkat Kemiskinan dan Pertumbuhan Ekonomi di Jawa Timur - Zaiyanul Fikram; Nurjihan Amanda Sikumbang; Amanda Revalina Br Ginting; Asnidar Asnidar; Ahmad Ridha (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to determine the effect of General Allocation Funds and Local Original Income on Poverty and Economic Growth in East Java. This study uses secondary data with a time series of 2014-2023 with the scope of East Java province. This research model uses a path analysis model using the eviews application. The results of this study indicate that the General Allocation Fund directly has a negative and insignificant effect on Poverty. Local Original Income directly has a negative and significant effect on Poverty. General Allocation Fund directly has a positive and insignificant effect on Economic Growth. Local Original Income directly has a negative and significant effect on Economic Growth. Poverty directly has a negative and significant effect on Economic Growth. Directly, the General Allocation Fund has a positive and insignificant effect on Economic Growth through poverty. Indirectly, Local Original Income has a positive and insignificant effect on Economic Growth through poverty.